(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The digital transformation of transport systems is a priority area worldwide and aims to improve the quality of the services offered, as well as the processes of planning and management of work and traffic in transport. Digitization allows in a qualitatively new way to compile basic technological documents, as well as to manage specific transport and business processes. Through such management, the transport of passengers and cargo becomes faster, more efficient and safer. The main problems in the construction of the new digital platforms are related to hardware and software collateral. This article discusses methodological and technical aspects of digital transport management models using new technical and technological solutions of specific business processes and systems management models. The specifics and main directions on which to work to improve the implementation and development of digital systems in transport are outlined.